1983
DOI: 10.1212/wnl.33.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Lipomembranous polycystic osteodysplasia (brain, bone, and fat disease)

Abstract: Progressive presenile dementia with lipomembranous polycystic osteodysplasia was first described by Jarvi and Hakola in an isolated region of Finland. We report the occurrence of this disorder in 4 of 10 siblings in an American family of Czechoslovakian ancestry. Characteristics of the disease include multiple bone cysts with pathologic fractures, progressive dementia with seizures and abnormal EEG, calcification of basal ganglia, and death in the fourth to six decades. Autosomal-recessive inheritance is likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The former three are essentially gray matter disease. White matter changes with axonal spheroids were first observed in a case of late infantile NAD and later found to be characteristic in several diseases, including Nasu-Hakola disease, dermatopathy-associated neuroaxonal leukodystrophy and hereditary diffuse leukoencephalopathy with axonal spheroids (HDLS) [4, 20, 21, 22, 23, 24]. In a thorough investigation of HDLS in a large Swedish pedigree, Axelsson et al [5]found that HDLS had clinical manifestations consisting of psychiatric symptoms, dementia and tetraplegia starting at the age of 39–65 years and was pathologically characterized by pronounced degeneration of axons and myelin with abundant axonal spheroids in the cerebral deep white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The former three are essentially gray matter disease. White matter changes with axonal spheroids were first observed in a case of late infantile NAD and later found to be characteristic in several diseases, including Nasu-Hakola disease, dermatopathy-associated neuroaxonal leukodystrophy and hereditary diffuse leukoencephalopathy with axonal spheroids (HDLS) [4, 20, 21, 22, 23, 24]. In a thorough investigation of HDLS in a large Swedish pedigree, Axelsson et al [5]found that HDLS had clinical manifestations consisting of psychiatric symptoms, dementia and tetraplegia starting at the age of 39–65 years and was pathologically characterized by pronounced degeneration of axons and myelin with abundant axonal spheroids in the cerebral deep white matter.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, the levels of Aβ deposition in postmortem NHD brains, where the biological function of TREM2/DAP12 signaling pathway is completely lost, remain unknown. A previous study reported a 48-year-old man of NHD with numerous senile plaques and neurofibrillary tangles throughout the cerebral cortex (12), suggesting that an impaired TREM2/DAP12 signaling function facilitates Aβ accumulation in the human brain. In the present study by immunohistochemistry, we investigate the expression of Aβ and p-tau in NHD brains to clarify whether the Alzheimer's disease pathology is augmented in NHD.…”
Section: Introductionmentioning
confidence: 96%
“…Together, these studies indicate that loss of TREM2 could trigger tau and A␤ pathology independently. It is interesting to note that senile plaques and neurofibrillary tangles have been observed in a brain autopsy of a 48-year-old patient clinically diagnosed with NHD and a homozygous mutation in TREM2 (90,91), suggesting that impaired TREM2 signaling might be sufficient to induce the two major neuropathological hallmarks of AD. However, the relative occurrence of AD characteristic neuropathology in NHD cases remains to be determined.…”
Section: How Could Mutations In Trem2 Contribute To the Risk Of Ad?mentioning
confidence: 99%